(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Laparoscopic surgery is associated with better pain experience, reduced Length of Hospital Stay and better scar. However, the resulting postoperative pain is distinct and can be disturbing, hence the need for multimodal analgesia. The side effects of parenteral analgesics and low practice of regional anaesthesia has limited their role in multimodal analgesia. Therefore, strategies that limit the reliance on these pain control modalities will be beneficial. Our study evaluated the efficacy of intraperitoneal instillation of plain bupivacaine after laparoscopic surgeries. The double blinded randomized study enrolled 50 consenting patients who fulfilled recruitment criteria. The bupivacaine group received 20mls of 0.25% plain Bupivacaine while the saline group received 20mls normal saline instillation into the peritoneal cavity via the umbilical port of the laparoscopy device. Visual Analogue Scale (VAS) was assessed at presentation at the Post anaesthesia care unit (PACU) and at 4, 8, 12, 16, 20, 24 hours afterward. In addition, the interval between end of surgery, first request for analgesia and total analgesic requirements were recorded. The VAS at presentation was significantly lower in the Bupivacaine group compared to the saline group, however, there was no statistically significant difference at other times. In addition, there was a significant difference in time to first analgesic request in both groups. The only observed post operative complications were nausea and vomiting. Intraperitoneal Instillation of Bupivacaine is an easy, non-invasive, cheaper and safer method of pain control following laparoscopic surgery in carefully selected patients.